Study of the heights of radar cloud tops in the Gangetic valley of West Bengal (MAUSAM, 1966)
Results of a study of the heights of radar cloud tops in the Gangetic valley of West Bengal based on hourly radar observations for the premonsoon and monsoon seasons of 1959 to 1962 are reported. Percentage frequency distributions at different height intervals and also during different periods of the day for two seasons under study and on a ten day period basis have been computed.